The Florida Cracker Horse: AN216/AN216, 4/2009 - Rey, Jorge R. (EDIS, 2009)
AN216, a 4-page illustrated fact sheet by Jorge Rey, describes this small breed of saddle horse designated “Florida’s Heritage Horse” by the Florida Legislature in 2008 — breed characteristics, history, current status, and events. Includes references. Published by the UF Department of Animal Sciences, April 2009.